ПРОЕКТУВАННЯ ЗМІСТУ ПРОФЕСІЙНО-ПЕДАГОГІЧНОЇ ПІДГОТОВКИ СТУДЕНТІВ ХУДОЖНЬО-ТВОРЧИХ СПЕЦІАЛЬНОСТЕЙ (Педагогіка вищої та середньої школи, 2022)
Planning of content of professionally pedagogical education of students of art creative specialities. In the article the features of professionally pedagogical education of students of creative higher educational establishment are examining, the criteria ofplanning of its maintenance are selecting.